The role of innovation in the relationship between digitalisation and economic and financial performance. A company-level research - Antonio Fernández-Portillo; Manuel Almodóvar-González; Mari Cruz Sánchez-Escobedo; José Luis Coca-Pérez (European Research on Management and Business Economics, 2022)
This paper analyses how innovation affects the relationship between the digitalisation of the company and its economic and financial performance, reviewing the cause-effect situation of this relationship. As some scientific literature suggests, the impact of ICT technologies on business performance is not homogenous amongst firms. The answer to this issue is probably to be found in innovation. In order to further develop this statement, this study examines the role of innovation in the relationship between business performance and business digitalisation. This research framework has been built based on the Innovation Theory of Rogers. Companies from all over Spain have been surveyed and the data has been contrasted with Partial Least Squares-Structural Equation modelling (PLS-SEM) and Moderation Analysis. The results show that in effect, innovation acts as a moderator variable in the relationship between business digitalisation and performance. These results allow us to conclude that it is not only important to digitalise the company to improve its performance, but that this digitalisation should also be aligned with a clear innovation strategy that allows for improving the company´s performance. The aim of this study is to contribute with greater knowledge to how the digitalisation of the company affects its economic/financial performance and manifest the role innovation plays in this relationship.